2021
DOI: 10.3389/fphar.2021.741261
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of TCMI in Patients With Combined Coronary Heart Disease and Heart Failure: A Systematic Review and Network Meta-Analysis

Abstract: Objective: To compare the efficacy and safety of conventional treatments (CTs) to those that included traditional Chinese medicine injections (TCMIs) in patients with combined coronary heart disease and heart failure (CHD-HF).Methods: Eight electronic literature databases (PubMed, Embase, Cochrane Central Register of Controlled Trials, Web of Science, China National Knowledge Infrastructure Database, Chinese Scientific Journal Database, Wanfang Database, Chinese Biomedical Database) were searched from their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Multiple epidemiologic studies have revealed that serum ACE levels are abnormally increased in patients with cardiovascular disease and hypertension and are connected to coronary artery stenosis. The renin-angiotensin-aldosterone system plays a significant role in the progression of cardiovascular disease [16]. In this study, smokers with CHD had significantly higher blood ACE levels than nonsmokers (control) (p<0.0001), suggesting that ACE may alter angiotensinogen 2 levels, which can lead to major consequences such as coronary heart disease.…”
Section: Discussionmentioning
confidence: 50%
“…Multiple epidemiologic studies have revealed that serum ACE levels are abnormally increased in patients with cardiovascular disease and hypertension and are connected to coronary artery stenosis. The renin-angiotensin-aldosterone system plays a significant role in the progression of cardiovascular disease [16]. In this study, smokers with CHD had significantly higher blood ACE levels than nonsmokers (control) (p<0.0001), suggesting that ACE may alter angiotensinogen 2 levels, which can lead to major consequences such as coronary heart disease.…”
Section: Discussionmentioning
confidence: 50%
“…After selecting the most up-to-date systematic review with the highest quality as the aforementioned method, there were 21 systematic reviews 18–38 left with 10 unique outcomes enrolled (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Yiqi Fumai lyophilized injection is accepted by most patients in China because of its effectiveness and safety, and can be used as an important supplementary drug for HF treatment. At a pathophysiological level, YQFM improves coronary blood flow, reduces myocardial oxygen consumption, inhibits inflammatory mediators, and reduces myocardial injury ( 24 ). The potential mechanism may be multifactorial.…”
Section: Discussionmentioning
confidence: 99%